Pengembangan E-Modul Kimia Lingkungan Berbasis Engineering Design Process Terintegrasi Socio-Scientific Issues untuk Meningkatkan Karakter Peduli Lingkungan Mahasiswa - Anik Pujiati; Kasih Haryo Basuki; Silvia Septhiani; Anita Febrianti (CV. Global Cendekia Inti, 2026)
This study aimed to develop an environmental chemistry e-module based on the Engineering Design Process (EDP) integrated with Socio-Scientific Issues (SSI) to improve students’ environmental care character. This study employed a Research and Development (R&D) method using a modified Borg and Gall model. The sample consisted of 19 students selected through purposive sampling. The research instruments included expert validation sheets, student response questionnaires, and pretest and posttest instruments for measuring environmental care character. The data were analyzed using descriptive statistics, N-gain, normality tests, and the Wilcoxon Signed Rank Test. The expert validation results showed that the e-module obtained an average score of 3.57, which was categorized as highly valid. The student response questionnaire obtained an average score of 4.22, which indicated a highly practical category. The average score of students’ environmental care character increased from 73.68 in the pretest to 82.37 in the posttest. The N-gain score was 0.33, indicating a moderate improvement. The Wilcoxon Signed Rank Test showed a significance value of 0.001, or p < 0.05, indicating a significant difference between the scores before and after the use of the e-module. These findings indicate that the EDP-based environmental chemistry e-module integrated with SSI is valid, practical, and effective in improving students’ environmental care character.